Chapter Un esercizio di immaginazione sociologica: se «*» e «ə» fossero persone? - STRIZZOLO, Nicola (Proceedings e report, 2023)
In the presentation, an exercise in sociological imagination is carried out: the question is asked if "*" and "ə" were people, what kind of gender would be projected onto them? The area in which an initial answer is sought is the world of entertainment, starting in particular with the Sanremo Festival 2022, co-hosted by actor Gianluca Gori as Drusilla Foer, in multiple chronicles celebrated as the most representative female face of this edition of the Festival. From an initial search of news images, we have shown how almost exclusively men are placed in the center and rewarded over women who use, express, manifest, and publicize aspects of themselves, in reference to gender, that are culturally ascribable to the other sex: a true gender inequality.